2007
DOI: 10.1002/ab.20204
|View full text |Cite
|
Sign up to set email alerts
|

Does empathy predict adolescents' bullying and defending behavior?

Abstract: Through structural equation modeling, this study tested a path of relations in which different levels of empathic responsiveness were posited to be differently associated to bullying and defending behavior. Three hundred and eighteen Italian adolescents (142 girls and 176 boys; mean age = 13.2 years) completed the Davis's Interpersonal Reactivity Index [Davis, 1983] for empathy and the Participant role scales [Salmivalli et al., 1996] for bullying and defending behavior. The results revealed that the model fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
286
6
38

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(367 citation statements)
references
References 54 publications
(83 reference statements)
26
286
6
38
Order By: Relevance
“…Other forms of bystander support in bullying include more direct, physical actions, such as actively defending the victim by responding directly to the bully (Pozzoli & Gini, 2010). Finally, bystanders might passively stand by, merely observing the episode (e.g., Gini et al, 2007). The following paragraphs review the extant literature related to each of these intervention behaviors.…”
Section: Bystander Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Other forms of bystander support in bullying include more direct, physical actions, such as actively defending the victim by responding directly to the bully (Pozzoli & Gini, 2010). Finally, bystanders might passively stand by, merely observing the episode (e.g., Gini et al, 2007). The following paragraphs review the extant literature related to each of these intervention behaviors.…”
Section: Bystander Behaviormentioning
confidence: 99%
“…Some research into traditional bullying (e.g., Gini et al, 2007) has found that empathy is linked to increased helping behavior. Additionally, the expression of empathy is often a central aspect of many online communities (e.g., Pfeil & Zaphiris, 2007).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In psychological circles, this construct is accepted as a multidimensional construct that includes cognitive and emotional components (11).…”
Section: Definition Of Empathymentioning
confidence: 99%
“…Στην ομάδα αυτή δεν έχει δοθεί ιδιαίτερη σημασία, αν και φαίνεται να παίζει ενεργό και καθοριστικό ρόλο, καθώς εμπλέκεται άμεσα στα εκφοβιστικά επεισόδια (Gini, Albiero, Benelli, & Altoe, 2007). Αρκετές έρευνες αναφέρουν ότι το ποσοστό των συμμαθητών και συνομηλίκων που είναι θεατές επεισοδίων εκφοβισμού ανέρχεται στο 85%-88% του μαθητικού πληθυσμού (Atlas & Pepler, 1998· Hawkins, Pepler, & Craig, 2001.…”
unclassified